AWARENESS ABOUT USING BECKS DEPRESSION INVENTORY AMONG DENTAL STUDENTS IN CLINICAL PRACTICE - Rani, Lakshya; Velayudhan, Ashok; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2020)
Depression is seen as a response or symptom of life stress or physical change and is not usually considered to reflect a mood disorder. There are many reasons for depression—familial and genetic influences. It is the tendency that makes people bring them into negative behaviour. The aim of the study is to assess the awareness about using the Becks Depression Inventory among dental students in clinical practice. A cross-sectional study was done with a self-administered questionnaire with 10 questions circulated among 100 dental students. The questionnaire assessed awareness about depression, clinical manifestations of depressive illness, psychological stress etiology of oral mucosal diseases, and usage of BDI questionnaires in practice. The responses were recorded and analysed.54% were aware of depression, and 46% were not aware of depression. 26% were aware of the clinical manifestation of depressive illness.32% were aware of the psychological stress etiology of oral mucosal diseases. 0% use the BDI questionnaire in practice. The awareness of BDI questionnaire usage in clinical practice among dental students was found to be low in this study. Our findings emphasize the importance of incorporating several educational and training programs for dental students to sensitize them to look for the psychological etiology of certain orofacial diseases.